Coral benchmarks in the center of biodiversity. Issue 2 (30th January 2017) - Licuanan, W.Y.; Robles, R.; Dygico, M.; Songco, A.; van Woesik, R.
Abstract: There is an urgent need to quantify coral reef benchmarks that assess changes and recovery rates through time and serve as goals for management. Yet, few studies have identified benchmarks for hard coral cover and diversity in the center of marine diversity. In this study, we estimated coral cover and generic diversity benchmarks on the Tubbataha reefs, the largest and best-enforced no-take marine protected area in the Philippines. The shallow (2–6 m) reef slopes of Tubbataha were monitored annually, from 2012 to 2015, using hierarchical sampling. Mean coral cover was 34% (σ ± 1.7) and generic diversity was 18 (σ ± 0.9) per 75 m by 25 m station. The southeastern leeward slopes supported on average 56% coral cover, whereas the northeastern windward slopes supported 30%, and the western slopes supported 18% coral cover. Generic diversity was more spatially homogeneous than coral cover. Graphical abstract: Highlights: Coral cover and generic diversity benchmarks are presented for the Tubbataha reefs. Average coral cover and average generic diversity were 34% and 18, respectively. 71% and 9% of the variance in coral cover was among sites and stations, respectively. 25% and 13% of the variance in generic diversity was evident among stations and sites. To date, the remoteness and high conservation status have provided resilience.